NGALAP IN BALINESE: A NATURAL SEMANTIC METALANGUAGE APPROACH - Suryasa, I Wayan (Lingual Journal of Language and Culture; Vol 1 No 1 (2016)DO - 10.24843/LJLC.2016.v01.i01.p07, 2016)
The research was intended to describe the meaning for producing the study that was postulated approach of natural semantic. In term of, one form for one meaning and one meaning revealed in a lexicon. This study was qualitative research that the data was anaction verb in Balinese language, it was “ngalap”pick. There were some lexicon to express the meaning of “pick”, those were ngancuk, ngotek, ngilit related to the high place of an entity, related to the low place can be expressed by ngilut, ngempok, mikpik, ngangap, and each lexicons have their meaning in expression. It could be thoroughly analyzed by Natural Semantic Metalanguage (NSM) theory. The unique findings shown by the instrument that used to do something, a juan was used to lexicons;ngancuk, ngotek, and ngilit, and hands was to do ngilut, ngempok, mikpik, ngangap. It meant, those lexicons used to express meaning in taking hold of something and move it. The entity was the high and low places.
Keywords: Balinese language, Ngalap, Metalanguage